An exploratory case study of food sharing practices in Caribbean countries through a transition lens using intergenerational dyad interviews - Anna Brugulat-Panés; Louise Foley; Madhuvanti M. Murphy; Nigel Unwin; Cornelia Guell (Globalization and Health, 2024)
Abstract Background Caribbean populations face complex health issues related to diet and food security as they undergo a rapid nutrition transition, resulting in some of the world’s highest number of premature deaths from noncommunicable diseases (NCDs). Despite policy efforts to promote local and regional food consumption, reliance on food imports remains high with many Caribbean countries importing more than 80% of their food from larger economies. Previous regional research revealed the importance of food sharing practices in the Caribbean, with implications for the consumption of local foods, food security, and community resilience against climate change. However, there is limited understanding of these practices and how they have evolved. Methods Using a transition lens, we explored the generational, life course, and sociocultural factors influencing food sharing practices in the Caribbean. We conducted semistructured online interviews with 10 intergenerational dyads involved in food sharing recruited from the virtual campus of the University of West Indies. Our study sample included 20 participants, ranging from 18 to 83 years old, from five English-speaking Caribbean countries (6 different islands). Results Food sharing practices had a central role within the social fabric of all participants, contributing to their mental health and well-being. They represented a fundamental aspect of participants’ culture and traditions, driving a sense of belonging and connection among Caribbean communities. However, contemporary food sharing practices indicated a move towards more convenience-oriented and processed foods, with reduced time spent cooking and a decline in the use of food sources such as backyard gardens, fishing, and marketplaces, with a preference for supermarkets. These trends, particularly observed among younger generations, aligned with the ongoing nutrition transition in the Caribbean and were influenced by various sociopolitical and environmental factors such as climate events, economic fluctuations, urbanisation, and changing family structures. Conclusions The evolving landscape of food sharing practices in the Caribbean has linkages with various domains of nutrition, health, society, culture, environment and globalisation. While a transition towards less healthy diets will increase the risk of many NCDs, the intrinsic cultural, social, and emotional benefits of food sharing could also positively impact health outcomes in the Caribbean region.